Improving Root Cause Analysis of Bacteriological Water Quality Failures at Water Treatment Works. (2015) - Ellis, K.; Mounce, S.R.; Ryan, B.; Biggs, C.A.; Templeton, M.R.
Abstract: Variations in spot-sampled and continuously-monitored water quality data were assessed to determine whether they could be linked to regulatory coliform failures. Data were available from raw water to the final monitoring point at water treatment works (WTW)-B and included climate, physico-chemical and bacteriological data. These were analysed using cross-correlation and self-organising maps in MATLAB®. The results highlighted rainfall and upstream coliforms and turbidity as important factors in the coliform failures. Further examination showed that failures correlated with low turbidity and low coliform loading, but relatively high rainfall. This outcome could be used to improve bacteriological compliance at WTW-B and similar sites.